ANALISIS SISA HASIL USAHA DITINJAU DARI PERPUTARAN PIUTANG DAN KAS PADA PUSAT KOPERASI KREDIT CARAKA UTAMA BANDAR LAMPUNG - Yohannnes P Kumagaya (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2018)
This research uses classical assumption test tools such as normality test, multicolinearity,heteroskidasticity, and autocorrelation and hypothesis test that is t test to know about the effect ofreceivable turnover and cash turnover toward rest of Business Result (SHU), test of R2to know theeffect of receivable turnover And the most influential Cash Turnover dominant against the SHU, F test toknow the effect of Receivable Turnover and Cash Turnover toward rest of Business Result (SHU)simultaneously, and then multiple linear regression test.This study shows that the data to be researched is normal, no multicolinearity, noheteroscedasticity and no autocorrelation occurs. In this study also shows that in T test known thattcount<ttable, and Fcount<FtableThe results showed that (1) Receivable turnover did not affect toward SHU because the level ofsignificance above 0.05 is 0.645, (2) the Cash turnover has no effect toward SHU because the level ofsignificance above 0.05 is 0.399, (3) The most dominant effect Is cash turnover, 35.6%, (4) receivableturnover and cash turnover together do not affect the rest of business result because Fcount<Ftable(0.776 <3.89).